Effect of Friction Welding Parameters for Aluminum and Copper - kurni, yahya kurniawan; Sitorus, Hivaldo Ricky; Tarigan, Joy Adithia (Universitas Riau Kepulauan, 2025)
Friction welding is a solid-state welding technique that generates heat from friction and pressure to join two metals together. Friction welding includes various techniques, such as friction stir welding, linear friction welding, and continuous drive friction welding. This literature review examines various friction welding techniques, the welding defects that may arise among these methods, and identifies the most appropriate friction welding technique for connecting pump shafts composed of Aluminum and Copper with a circular cross-section, as fusion welding is not applicable for joining Aluminum and Copper. A primary reason is the substantial difference in melting temperature between Aluminum and Copper, approximately. 400 degrees Celsius. Based on the literature review, the outcomes of friction welding may be influenced by rotational speed, duration of pressure, axial pressure force, and the properties of the materials utilized. Employing a case study of the pump shaft, it was determined that the continuous drive friction method is the optimal technique for bonding Aluminum and Copper in the pump shaft, as the temperature distribution can be uniform across the entire weld joint surface. This situation will lead to a more uniform microstructure and weld joint quality.